Effect of alkaline treatment on the thermal and mechanical properties of sugar palm fibre reinforced thermoplastic polyurethane composites - Bachtiar, Dandi; Mohammed, Ausama Abbas; Palanisamy, Sivasubramanian; Imran, Al Ichlas; Siregar, Januar Parlaungan; Mohd Ruzaimi, Mat Rejab; Syaubari, Syaubari; Cionita, Tezara; Fitriyana, Deni Fajar; Al-Farraj, Saleh A.; Almansour, Mansour I; Ma, Quanjin (Nature Publishing Group, 2025)
This study examines the impact of alkaline treatment on the mechanical, thermal, and morphological properties of sugar palm fiber (SPF)-reinforced thermoplastic polyurethane (TPU) composites. SPF fibers (250 μm) were treated with sodium hydroxide (NaOH) solutions of 0%, 2%, 4%, and 6% (w/w) for 90 min at room temperature. These fibers were then mixed with TPU in an extruder at 180–200 °C and molded into composite sheets using compression molding at 190 °C, 10 MPa pressure, and a 10-minute holding time. X-ray diffraction (XRD) revealed increased crystallinity in the composites, peaking at 1589 cps with 6% NaOH. Fourier transform infrared (FTIR) spectra showed improved fiber-matrix compatibility, most evident with 2% NaOH. SEM analysis indicated cleaner and rougher fiber surfaces post-treatment, though cracks were observed at higher concentrations. Energy-dispersive X-ray (EDX) confirmed increased oxygen content and sodium residue at elevated NaOH levels, reflecting lignin removal. Thermogravimetric analysis (TGA) demonstrated enhanced thermal stability, with the highest residue mass of 599.16 °C at 6% NaOH. Alkaline treatment notably enhanced SPF/TPU composites, with 2% NaOH providing optimal flexural strength and 6% NaOH maximizing impact strength and thermal stability.